Contribution of Self-efficacy and Optimism on Nurse Work Engagement - Nisa Dewanti; Mira Melynda Prakosa (Fundamental and Management Nursing Journal, 2024)
Introduction: Work engagement for nurses is needed to increase dedication so that health organizations run effectively and efficiently. Self-efficacy and optimism are components of personal resources that can predict work engagement. This research aims to see the contribution of the role of self-efficacy and optimism to nurses' work engagement. Methods: This was a cross-sectional study. A cluster sampling technique was used to recruit 130 nurses.  Data on self-efficacy, optimism, and nurse work engagement were collected by questionnaire, and analyzed by logistic regression techniques. Results: Self-efficacy and optimism in nurses had a significant effect on nurse work engagement with the sig values 0.011 and 0.000. These make nurses more persistent, enthusiastic, and focused at work. Conclusions: Nurses who have high self-efficacy are always confident in their abilities. Likewise, nurses who have high optimism tend to be more confident and have high persistence at work, so that work engagement will be formed well. Future studies should place greater emphasis on exploring new nurse’s self-efficacy and optimism.